Eat that frog! action workbook - Tracy, Brian (Berrett-Koehler Publishers, 2017)
The workbook follows the same twenty-one-chapter format as the book. Each chapter includes four exercises with space to do the exercises on the pages. The workbook will also include a narrative character who is struggling with procrastination in her work and home lives and uses the recommendations from Eat That Frog! to improve her time management performance.
"A BK Life book.". - Includes bibliographical references. - Online resource; title from title page (Safari, viewed July 31, 2017)
Keywords: Procrastination; Success in business; Succès dans les affaires